Legal Analysis of Transparency on the Implementation of The ASEAN Trade in Services Agreement (ATISA) - Koesrianti, Koesrianti; Tanega, Joseph (Universitas Negeri Semarang, 2025)
In international trading system, trade in services covers a wide range of intangible and heterogeneous products and activities which making it complex in the implementation phase. Association of Southeast Asian Nations (ASEAN) had established a progressive agreement on trade in services, the ASEAN Trade in Services Agreement (ATISA) that brings trade liberalization on services by recognizing progressive negative list approach. Nevertheless, there is no clear framework on how this agreement will be applied as ASEAN Member States (AMS) have difference economic policies considered the complexities of services sector. This paper aims to explore the regulation on trade in services, in particular the legal analysis of transparency of the implementation of the negative list approach brought by ATISA. This new agreement has a built-in agenda for AMS to convert their previous commitments of positive approach under ASEAN Framework Agreement on Services (AFAS). This paper is a doctrinal research based on secondary data by analysing the existing international legal instruments on trade, ASEAN agreements and policies on the liberalization of trade in services in the context of the ASEAN single market and production base as well as epicentre of growth. Despite its’ potential benefits of ATISA, this article identifies substantial challenges in implementing newly trade in services agreement in ASEAN. This article argues that ASEAN still needs improving the regulatory standards for the service sector and reducing the unnecessary barriers to service trade within ASEAN, as well as increasing the respective regulatory transparency in each AMS.